Iapar 5-Rio Piquiri’ and ’Iapar 7-Rio Vermelho’, new varieties of dry-bean for the State of Paraná - Alberini, João Luiz; Kranz, Walter Miguel; Oliari, Lourenço; Bianchini, Anésio (Pesquisa Agropecuaria Brasileira, 2014)
After three cycles of selection under controlled conditions and three cycles of selection under natural conditions in segregating populations that resulted from crosses of ’Cornell 49-242’ (source of resistance to six physiologic races of the fungus Colletotrichum lindemuthianum) with the varieties ’Aroana’ and ’Roxo Minas’, the promising lines RAI 12, RAI 46 and RAI 53 were created. Results of three years of trials with these lines compared to the variety ’Carioca’ in fourteen localities in the State of Paraná, Brazil, are presented. Based on data of yield, adaptation and reaction to diseases (rust and anthracnose), RAI 46 and RAI 53 were mixed and released under the name of ’IAPAR 5-Rio Piquiri’; the new variety has a lusterless light-brown seed coat with purplish halo: the average weight of 1.000 seeds is around 265 grams. RAI 12 was released under the name of ’IAPAR 5-Rio Vermelho’ and its seeds have a dull-purple seed coat; the average weight of 1.000 seeds is around 255 grams, The new varieties of beans (Phaseolus vulgaris L.) were recommended for planting in the North Region of Parana and their main characteristics are presented.